2021
DOI: 10.3390/molecules26164976
|View full text |Cite
|
Sign up to set email alerts
|

Biological Activities of Paeonol in Cardiovascular Diseases: A Review

Abstract: Paeonol is a naturally existing bioactive compound found in the root bark of Paeonia suffruticosa and it is traditionally used in Chinese medicine for the prevention and management of cardiovascular diseases. To date, a great deal of studies has been reported on the pharmacological effects of paeonol and its mechanisms of action in various diseases and conditions. In this review, the underlying mechanism of action of paeonol in cardiovascular disease has been elucidated. Recent studies have revealed that paeon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 110 publications
(143 reference statements)
0
15
0
Order By: Relevance
“…Paeonol is a natural phenolic compound present in the root bark of Paeonia suffruticosa and was reported by previous studies to modulate oxidative, inflammatory, and apoptotic pathways, as well as has antitumor properties (Zhang et al, 2019;Vellasamy et al, 2021). Few in vitro studies have shown that paeonol might modulate the expression of efflux transporters that accept MTX as a substrate, such as BCRP and P-gp (Zhang et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Paeonol is a natural phenolic compound present in the root bark of Paeonia suffruticosa and was reported by previous studies to modulate oxidative, inflammatory, and apoptotic pathways, as well as has antitumor properties (Zhang et al, 2019;Vellasamy et al, 2021). Few in vitro studies have shown that paeonol might modulate the expression of efflux transporters that accept MTX as a substrate, such as BCRP and P-gp (Zhang et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…39 Paeonol in Paeonia suffruticosa, one of the crude drugs used to resolve blood stasis, improves endothelium injury. 40 Endothelial damage is considered responsible for long COVID; therefore, blood stasisresolving formulae may be suitable for treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Paeonol has the effect of treating cardiovascular and cerebrovascular diseases, such as lipid-lowering and anti-atherosclerosis, vasodilation and blood pressure lowering, anti-arrhythmia, anti-cerebral ischemia-reperfusion injury and neuroprotection. It also has anti-hepatic injury and liver fibrosis, anti-inflammatory, antibacterial activity, anti-inflammatory activity, antioxidant activity and anti-tumor activity ( 215 217 ). Paeonol also decreased IL-1β immunoreactive cell numbers and microglia/macrophage activation in the ischemic brain ( 218 ).…”
Section: Modulatory Effects Of Natural Botanical Components On Microg...mentioning
confidence: 99%